METODE PEMBELAJARAN PERMAINAN BOLA TANGAN DENGAN MENGGUNAKAN LATIHAN LADDER DRILL HOP SCOTCH PENGARUHNYA TERHADAP KEMAMPUAN AGILITY BERMAIN BOLA TANGAN - Rohman, Ujang (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2018)
This research is motivated by the fact that teaching in activities Students of the 2015 Sports Coaching Education, the Teaching and Education Faculty of the University of PGRI Adi Buana Surabaya the delivery of training materials less than the maximum, so that learners become passive and processes running less interesting extracurricular activities. Agility on hand ball sport is a absolut needs wich is must be had by all of hand ball’s atletes. Formulation of the problem in this research is